Strategies for translating Chinese culture-specific items into English in Mo Yan's Red Sorghum - Zuo, Yunchao (2023)
The translation of culture-specific items (hereafter CSIs) from the source language into the target language is challenging due to the difficulty in finding corresponding words with the same status or meaning. This is particularly true for languages that differ significantly in their linguistic features and cultural implications. For example, the Chinese language belongs to the Sino-Tibetan language family, while the English language belongs to the Indo-European language family. Accordingly, the two languages have different cultural connotations in terms of customs, religious habits and historical backgrounds, which may lead to cultural distortions, losses and conflicts in culture (Li et al., 2010). In addition, the difficulty of translating CSIs in the novel Red Sorghum is exacerbated by the many strange and unfamiliar languages used by the author. Although previous studies have examined the translation strategies of CSIs, few studies have explored the translations of CSIs in the novel Red Sorghum based on Functionalist Translation Theory (1996) and Aixelá's translation strategies (2007). Therefore, this study focuses on the following research objectives: 1. To identify the English translations of CSIs in Red Sorghum by Goldblatt; 2. To analyse the strategies employed in the English translation of CSIs in Red Sorghum by Goldblatt; 3. To discuss the impacts of translation strategies in rendering CSIs in Red Sorghum into English. The research data encompasses culture-specific items (CSIs) found in Mo Yan's Red Sorghum and their corresponding English translations by Howard Goldblatt. Following the methodologies of Aixelá (2007) and Nida (2007), instances of CSIs are extracted and classified. A qualitative approach is then employed to analyze the translation strategies. The key findings of the study reveal that linguistic translation and absolute universalization are the most frequently used strategies across all types of CSIs. Different types of CSIs necessitate different translation approaches, with linguistic translation proving particularly effective for linguistic and religious CSIs. Meanwhile, social CSIs benefit from a combination of linguistic translation and orthographic adaptation. Moreover, the study underscores the importance of adhering to an aesthetic rule in translation to preserve the artistic value of the original text. The implications of this research extend to both translation theory and practice, emphasizing the positive impact of selecting appropriate strategies when dealing with CSIs. The theoretical significance lies in the applicability of the research framework established here to other translations of literary works. On a practical level, this study aids in fostering an understanding and appreciation of translated texts, assisting translation students and practitioners in enhancing the quality of their translations.